2015
DOI: 10.7554/elife.11092
|View full text |Cite
|
Sign up to set email alerts
|

Odor-identity dependent motor programs underlie behavioral responses to odors

Abstract: All animals use olfactory information to perform tasks essential to their survival. Odors typically activate multiple olfactory receptor neuron (ORN) classes and are therefore represented by the patterns of active ORNs. How the patterns of active ORN classes are decoded to drive behavior is under intense investigation. In this study, using Drosophila as a model system, we investigate the logic by which odors modulate locomotion. We designed a novel behavioral arena in which we could examine a fly’s locomotion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
81
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(90 citation statements)
references
References 65 publications
(82 reference statements)
9
81
0
Order By: Relevance
“…As expected, flies were more likely to be oriented upwind when the odor was on ( Figure 2C), as previously reported [14,18,[20][21][22][23]49]. However, unlike for flies walking into a spatially homogeneous odor block [20,39,40], changes in average angular speed were minor, with a less than 10% change between blocks ( Figure 2D). Walking speeds were similarly unmodulated, again in contrast to walking flies in homogenous odor blocks ( Figure 2E) [20].…”
Section: Stopping and Turning Comprise The Bulk Of The Navigational Rsupporting
confidence: 86%
See 2 more Smart Citations
“…As expected, flies were more likely to be oriented upwind when the odor was on ( Figure 2C), as previously reported [14,18,[20][21][22][23]49]. However, unlike for flies walking into a spatially homogeneous odor block [20,39,40], changes in average angular speed were minor, with a less than 10% change between blocks ( Figure 2D). Walking speeds were similarly unmodulated, again in contrast to walking flies in homogenous odor blocks ( Figure 2E) [20].…”
Section: Stopping and Turning Comprise The Bulk Of The Navigational Rsupporting
confidence: 86%
“…It is surprising that despite the rich locomotive repertoire of walking Drosophila, a large part of their olfactory navigational strategy can be reduced to four actionsleft turn, right turn, walk and stop. Still, we expect that differences in wind conditions and in odor identity and valence might modulate finer motor control in navigation [39]. A recent, systematic study of the locomotive structure of walking Drosophila in various odor environments without horizontal wind has found that behaviors fall into a limited number of states comprising a hierarchical hidden Markov model [57].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The low dimensionality of olfactory behavior in our data is likely a consequence of the simple experimental paradigm we have used. In other contexts, olfactory behavior may have a higher dimensionality (Jung et al, 2015). …”
Section: Resultsmentioning
confidence: 99%
“…For example, flies modulate their locomotor activity in response to many stimuli, such as odors with different biological significance. 40) Another recent study reported that locomotor activity influences sugar preference behavior. 41) Advances in these studies are based on emerging computational image analysis techniques, which enable the measurement of multiple behavioral parameters of individual flies.…”
Section: Discussionmentioning
confidence: 99%